Investigation on migration of LNAPL and DNAPL in different sand size layers - Tan, Siew Leng (2017)
Soil contamination can be caused by any hazardous liquid, but namely hydrocarbons, which may be spilled or buried directly in the soil or migrate to the soil from elsewhere. When soil contamination occurs, it will cause groundwater pollution as well due to the movement of contaminants in the soil. The contaminants studied in this project are commonly referred to as non-aqueous phase liquids (NAPLs), which will dissolve slightly in water. Therefore, it is important to study the migration of NAPLs in soil. The main objective of this research is to investigate the migration of two different NAPLs in different sand size layers. Two types of NAPLs were used, which are toluene and trichloroethylene. Four different sizes of sand were used, which are 1.18 mm, 0.60 mm, 0.30 mm and 0.15 mm. Each NAPL was poured into the acrylic model after the preparation of the sand sample was ready. A digital camera was used to capture the images and Image-Pro software was used to process the data needed. The migrations of both NAPLs were analyzed through the image captured and data processed from the image software. From the experimental work, it showed that the time taken for the migration of NAPL is affected by the pore size in the sand layer. The percent area of NAPL migration can be generated by the imaging software. The percent area also can be affected by several characteristics such as interfacial tension, capillary pressure, gravitational force and density of NAPL with the interaction with pore sizes in sand layer. Other than that, the migration of NAPL will flow through the pathway with least resistance and does not have equal spreading in the sand layer.